Using Audio Lingual Method to Improve Students Pronunciation Ability of Darul Mahdiah Private School - Hikmah Hidayati, Kuni (ELLITE, 2016)
This study aims at finding out how the use Audio Lingual Method through Repetition Drill Technique improves Thai students’ pronunciation ability. This is a Classroom Action Research (CAR) conducted in Darul Mahdiah private school Songkhla-Thailand. The subjects of the study are 16 Thai students of class 6/2 at the school. The data were collected from pronunciation tests and analyzed by using percentages analysis. The result of the students’ pronunciation improvement was as follows; in the pre-pronunciation test the students’ pronunciation score was 0% (excellent), 0% (very good), 31.25% (good), 31.25% (low) and 37.5% (failed), in the cycle 1 post test the score was 0% (excellent), 14.29% (very good), 50% (good), 21.42% (low) and 14.29% (failed), and the score of the cycle 2 post test was 6.25% (excellent), 37.5% (very good), 43.75% (good), 12.5% (low) and 0% (failed). This leads to the conclusion that the students’ improved pronunciation was due to the two reasons; first, the students’ pronunciation ability improved through repetition drill since they got used to pronounce words intelligibly as what the teacher modeled.Keywords: audio lingual method, repetition drill, pronunciation, thai students